Manajemen Rantai Pasok Benih Cabai Rawit (Kasus di Yayasan Idep, Desa Batuan Kaler, Kecamatan Sukawati, Kabupaten Gianyar) - WIDISATRIANI, GUSTI AYU; WIDYANTARA, I WAYAN; ANGRENI, I.G.A.A.LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Supply Chain Management of Chili Seeds (Case of Idep Foundation, Desa Batuan Kaler, Sub-district Sukawati, Gianyar regency) The purpose of this study is to find out about supply chain management of chili seeds from the producer to the consumer that is conducted and to find out about the efficiency of chili seeds supply chain management on Idep Foundation. The variables analyzed were supply chain and efficiency. There are three indicators in the supply chain variables, namely (1) the pattern of supply chain, (2) marketing margin and (3) the pattern of the value chain. While the efficiency variables consists of two indicators: (1) technical efficiency index and (2) economic efficiency index.Based on the results of the analysis can be concluded that there are six kind of supply chain in Yayasan Idep that include Yayasan Idep as suplier, distributor, and retailer. Lowest supply chain contained in the supply chain that only involving suplier with Rp 5.200,00. While the supply chain that involving distributor and retailer has the same margin in the amount of Rp 6.900,00. The most technically efficient supply chain is the supply chain that involving suplier that is equal to 0 gr/km. While the most economically efficient supply chain contained in supply chain that involving distributor and retailer in the amount of Rp 1,02. Keywords: chili seeds, supply chain, marketing margins and efficiency